Please help me I beg you! :(
pegah avatar

Answers

Answer 1
Answer: Question 6

x² - 16 = 0
x² = 16
x² = √16
x = 4 or -4

Question 7

x²  + 3x - 54 = 0
Factorizing

Find two numbers that add to make 3x and multiply to make 54
Write out the factor of -54 in pairs
1, -54
-1, 54
2, -27
-2, 27
3, -18
-3, 18
4, -16
-4, 16
6, -9
-6, 9
Then find the pair that, when added = +3 (in bold)
-6 + 9 = 3

x² + 9 - 6x - 54 = 0
x(x + 9)      -6(x + 9)

Use the (x + 9) and the coefficient of these brackets to make double brackets.
(x+9)(x-6) = 0

If the product of two terms =0, at least one must equal 0

x + 9 = 0
x = -9

x - 6 = 0
x = 6

x = -9 or 6


Question 8

2x² -11x - 6 = 0

First, multiply the coefficient of x² by the value of c (the number on its own)2 x -6 = 12

This time, find factors of -12 that equal -11
1, -12
-1, 12
2, -6
-2, 6
3, -4
-3, 4
The pair is in bold
1 + -12 = -11

2x² -12x + x - 6
Split down the middle and factorise in singe brackets
2x(x - 6)        1(x - 6)
Now use the brackets pre-made (x - 6) and put together what is in front of them (2x +1)
(2x + 1)(x - 6)

 If the product of two or more terms = 0, at least 1 must equal 0
2x + 1 = 0
2x = -1
2x/2 = x       -1/2 = -0.5

x - 6 = 0
x = 6

x = -0.5 or 6
Answer 2
Answer:
Question #6:
They expect you to remember that the difference
of two squares can be factored as 

   (the sum of the squared numbers) times (their difference).

So   [ x² - 16 = 0 ]  can be written as  (x + 4) (x - 4) = 0 .

Now, a rule that you've used hundreds of times before
and you'll use thousands of times again: 
If the equation says that the product of two things is zero,
then the equation is true if EITHER of them is zero.

So ...  
(x+4) = 0 gives you one solution,
and (x-4)=0 gives you the other solution.
__________________________________

Question #7:

Factor the left side of the equation.

       (x + 9) (x - 6) = 0 .

Now, use a rule that you heard somewhere VERY recently:
If the equation says that the product of two things is zero,
then the equation is true if EITHER of them is zero.

So ...
(x + 9) = 0 gives you one solution, and
(x - 6) gives you the other one.
_______________________________________

Question #8:

Factor the left side of the equation:

           (2x + 1) (x - 6) = 0

Now use the golden rule that you've memorized by now:
If the equation says that the product of two things is zero,
then the equation is true if EITHER of them is zero.

So ...
(2x + 1) = 0 gives you one solution,
and (x - 6) = 0 gives you the other one.




Related Questions

Suppose a crew member at an unloading dock can unload 3 trucks per hour and have already unloaded 17 trucks. Which equation can be used to medel the number of trucks the crew unloads after h hours?A. 3h+17B. 3h=17C. 17h-3D. 17h+3
Please help me! im really stuck on this one!
How many whole numbers have exactly 3 digits
A store sells 8 cans of nuts for $20 how much would it cost to buy 7 cans of nuts?
The cost C (in dollars) of making n feet of cabinet is represented by C = 18n + 45.How many feet of cabinet are made when cost is $144?

Jason baked 7 pans of brownies. He gave 1/4 of the brownies to his two sisters. How many pans of brownies did he give to his sister's?​

Answers

like two of them

hope this helps

In your own words explain the place-value relationship when the same two digits are next to each other in a multi-digit number

Answers

the one to the left is bigger thatn they other one by 10 times aka
the one to the left is 10 times bigger than the one to the right

Solve for x. x2 + 7x + 10 = 0

Answers

the answer is negative 80 or like this -80

When the perimeter of a rectangle is 68ft. and the ratio of it's length to it's width is9:8. What are the dimensions of the rectangle and how do you come about the answer?

Answers

rectangle's perimeter formula is p=2(length+width)
2(9x+8x)=68
17x=34
x=2
length is 9(2)=18 feet
width is 8(2)=16feet

Answer:

length is 9(2)=18 feet

width is 8(2)=16 feet

Step-by-step explanation:

rectangular perimeter formula is length plus width

2 ( 9x +  x ) = 68

17x = 34

x = 2

please rate and mark brainiest if this helped.

Use the number 382 to write a subtraction equation in which only tens is ungrouped.

Answers

Answer:

382 - 33 =  349

382- 44 = 338

382 - 35 = 347

Step-by-step explanation:

First let's see what ungroup is.

We are given a number 382

If ungroup this number, we get 3 hundreds 8 tens and 2 ones.

This is called ungrouped.

We are asked to write the subtraction equation in which only tens is ungrouped.

So we need to use the number 382 where only tens place should be ungrouped.

Here the tens place value digit is 8, it means there are 8 tens.(8 *10 = 80)

So we need to subtract a number such that tens should be ungrouped in 382.

The number that should have one's place should be greater that 2, then only we can ungroup tens in the number 382.

We can have many such numbers, 33, 34. 35. 36. 39, 43, 44, 45 and so on.

We can use any of those numbers subtract from 382 in which only tens is ungrouped.

382 - 33 =  349

In 33, the ones place is 3  and in 382 ones place is 2. We cannot subtract 3 from 2.

So we ungroup tens, there 8 tens, we take 1 tens and brake into 10 ones.

Now we will have (10 +2 = 12 ones) from 12 ones we subtract 3 ones, so we get 9 on the ones place.

Similarly, we can write many subtraction equation using the number 382 in which only tens is ungrouped.

382- 44 = 338

382 - 35 = 347

and so on.

382-40=342 I think is the answer

If 50 is 20% of a value what is that value

Answers

The answer would be 200 because it takes 20% 4x to get to 100% so 50x4=200
The value would be 250.
Other Questions